Beta-adrenergic stimulation of calcium channels occurs by potentiation of high-activity gating modes. - Yue, D T (1990)
cAMP-dependent phosphorylation clearly increases current through cardiac L-type Ca channels, but the molecular manifestation of this effect remains controversial. Previous work implicates either an increase in the number of functional channels or graded changes in the gating of individual channels. We now find that single cardiac Ca channels display three patterns of activity ("modes") and that isoproterenol or 8-bromoadenosine 3',5'-cyclic monophosphate redistributes the relative proportions of modes such that the two most active (mode 1, bursts of brief openings; mode 2, very long-lasting openings) are favored (P less than 0.05; n = 7). Conversely, a pattern of sparse brief openings (mode 0a) is selectively inhibited (P less than 0.01). Despite differences in the relative frequencies of the various modes before and during drug exposure, the gating within each mode is not detectably changed. We conclude that potentiation of highly active modes of Ca channel gating underlies the enhancement of calcium influx by beta-adrenergic stimulation.